Early feeding after total laryngectomy results in shorter hospital stay without increased risk of complications: a retrospective case–control study. (December 2015) - Serbanescu‐Kele, C.M.C.; Halmos, G.B.; Wedman, J.; van der Laan, B.F.A.M.; Plaat, B.E.C.
Abstract : Objectives: To evaluate the effects of a reduced nil per os (NPO) period after total laryngectomy (TLE) on general and wound‐related post‐operative complications, swallowing function and duration of hospital stay. Design, setting and participants: In a retrospective case–control study in 71 patients after TLE with primary closure (i e. without reconstruction with tissue transfer), complications and hospitalisation in 36 patients who started oral feeding on days 3–5 (early feeding) were compared with 30 patients who started oral feeding on days 7–10 (late feeding). Main outcome measures: Incidence of complications, swallowing function and duration of hospitalisation. Results: There were no significant differences between the early‐ and late‐feeding groups in the occurrence of pharyngocutaneous fistulae, neopharyngeal stenosis or wound complications in general. Swallowing function was comparable for both groups. Mean overall hospitalisation was 2 days shorter in the early‐feeding group (mean: 17.4 days) as compared to the late‐feeding group (mean: 19.4 days) ( P < 0.05). Conclusions: Early feeding after TLE without flap reconstruction did not contribute to an increase in complications and led to a shorter hospital stay.